Strategic Management Accounting and Strategic Management: The Mediating Effect of Performance Evaluation and Rewarding - Petera, Petr; Wagner, Jaroslav; Šoljaková, Libuše (International Journal of Industrial Engineering and Management, 2020)
The purpose of this article is to investigate the mediating effect of performance evaluation and rewarding on the implementation of strategic management accounting (SMA) into strategic management. Although these issues have important consequences for managerial practice, they have yet to be empirically addressed by previous studies making this research more significant. A model was proposed and tested using partial least squares modeling. Data were collected via questionnaire from a random sample of 90 medium- and large-size businesses with two lines of mediation being considered. The first involves performance evaluation and performance-based rewarding of top management, while the second concerns the evaluation and rewarding of middle- and lower-level managers. A mediating effect does exist and is relatively strong. A practical implication of this study is the recommendation that companies should support the implementation of SMA into strategic management via performance evaluation of all managerial levels and performance-based rewarding of top managers. For middle- and lower-level managers, strategic performance-based rewards need to be carefully considered. Theoretically, this study pioneers the investigation of variables other than company performance as a dependent variable in SMA. Article history: Received (December 18, 2019); Revised (April 30, 2020); Accepted (May 05, 2020); Published online (May 19, 2020)